Enhancing Battlefield Awareness: Integration of IoMT Sensors and Networks in National Defense Systems - Sarjito, Aris; Lelyana, Nora (Jurnal Ilmu Sosial dan Humaniora, 2024)
The integration of the Internet of Military Things (IoMT) into national defense systems presents both opportunities and challenges for enhancing battlefield awareness and decision-making. This study explores the technical and operational barriers to IoMT deployment, such as interoperability, network bandwidth limitations, energy consumption, and cybersecurity vulnerabilities. Using qualitative research methods based on secondary data from academic articles, defense reports, and technical documents, the study investigates how these challenges impede the effective use of IoMT in military operations. The research findings highlight key issues such as the lack of standardized communication protocols across devices, the need for low-latency networks, and the heightened cybersecurity risks posed by a large number of interconnected devices. Furthermore, the study underscores the importance of energy-efficient solutions to ensure continuous device operation in combat zones. Conclusions suggest that addressing these challenges through standardization, enhanced cybersecurity measures, and adopting emerging technologies such as AI and blockchain is essential for realizing IoMT's potential. Future research should focus on human and organizational factors, geopolitical concerns, and sustainability in IoMT deployment.